EXTERNAL VARIATION IN LANGUAGE STUDY OF LANGUAGE VARIATION BASED ON PERSPECTIVE SOCIOLINGUISTICS - Afham Muqowwam, Febrayani Agata Rumasondi, Avita Putri Hariani (Integrative Perspectives of Social and Science Journal, 2025)
External language variation is a phenomenon where a language undergoes changes due to influences from other languages or dialects. This phenomenon frequently occurs in multicultural societies with exposure to multiple languages, and in the context of globalization, which accelerates linguistic interactions. This paper discusses external language variation as a significant aspect of sociolinguistics, focusing on its causes, forms, and the social and cultural impacts it produces. This study highlights how interlingual contact leads to loanwords, grammatical assimilation, and phonological shifts. Examples from various languages, including the influence of English on local languages, illustrate how external language variation affects identity and language continuity.